Kewenangan Dinas Pekerjaan Umum Pada Dinas PU (Pekerjaan Umum) Kabupaten Muaro Jambi - Endang Meiliani; Sopian Sopian (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2021)
In this study using a qualitative approach, namely to find out or describe the reality of the events under study. Data collection instruments used by researchers are: Observation, Interview, Documentation. Based on Law Number 23 of 2014 concerning Regional Government (State Gazette of the Republic of Indonesia Chapter IV Government Affairs). Authority is a very important thing in government because one of the main principles that is used as the basis for every government and state administration in every state law in exercising its authority must be based on the applicable laws or legal regulations (legality principle). the implementation of the authority of the Public Works and regional offices at the Public Works (Public Works) Office of Muaro Jambi Regency. Community participation, that community participation is very important in carrying out development. The use of APBD funds that have been allocated for regional road management activities must be adjusted to the priority scale. The Strategic Planning of the PUPR Office of Muaro Jambi Regency was formulated as a form of commitment of the PUPR Office ranks in increasing the accountability of the performance of government agencies as stipulated in the vision, mission, goals, and objectives.